Transport for people with a mobility handicap - Seminar on Transport for People with a Mobility Handicap (1993 : University of Manchester Institute of Technology); Planning and Transport Research and Computation International Association; PTRC Transport, Highways and Planning Summer Meeting (21st : 1993 : University of Manchester Institute of Science and Technology) (London : PTRC Education and Research Service, 1993)
08